Analisis Pengaruh Perceived Customer Value, Price, dan Brand Image terhadap Customer Loyalty Melalui Customer Satisfaction sebagai Variabel Intervening: Studi pada Pelanggan Konsumen Brand Erigo di Semarang - Helena Siregar; Amie Kusumawardhani (Faculty of Economics and Business Diponegoro University, 2025)
Erigo is one of the most popular brands among young people. As a rising local fashion brand that actively markets its products through social media and online stores, Erigo must implement an effective marketing strategy to enhance customer loyalty, which is crucial for sustaining its position in the highly competitive industry. This research conducted on consumers who have purchased Erigo products and domiciled in Semarang.This study uses a sample of 165 respondents were used as samples in this research. Data collection was conducted through a questionnaire using purposive sampling method, and analysis was performed using Structural Equation Modeling (SEM) through AMOS 24.The results showed indicate that customer satisfaction has a positive but insignificant influence on customer loyalty, price has a positive but insignificant influence on customer loyalty, perceived customer value has a positive and significant influence on customer loyalty, brand image has a positive and significant influence on customer loyalty, perceived customer value has a positive and significant influence on customer satisfaction, price has a positive and significant influence on customer satisfaction, and brand image has a positive and significant influence on customer satisfaction.